The behavioral intention to adopt mobile health services: The moderating impact of mobile self-efficacy - Mensah, Isaac Kofi; Zeng, Guohua; Mwakapesa, Deborah Simon (Frontiers in Public Health, 2022)
This study explored the moderating impact of mobile self-efficacy on the adoption of mobile health services. The UTAUT was used as the theoretical foundation for this study. The results have indicated that mobile self-efficacy was significant in moderating the impact of both performance expectancy (β = −0.005, p < 0.05) and effort expectancy (β = −010, p < 0.05) on the adoption of mobile health services. In addition, it was revealed to our surprise that both performance (β = 0.521, t = 9.311, p > 0.05) and effort expectancy (β = 0.406, t = 7.577, p > 0.05) do not determine the behavioral intention to use mobile health services. Effort expectancy and behavioral intention to use were also, respectively, not significant in influencing performance expectancy (β = 0.702, t = 12.601, p > 0.05) and intention to recommend the adoption of mobile health services (β = 0.866, t = 13.814, p > 0.05). Mobile self-efficacy, however, was found to significantly predict the citizen's intention to recommend the adoption of mobile health services (β = 0.139, t = 2.548, p < 0.05). The implications of these findings on mobile health are discussed.